It’s Just Conservation: To What Extent Are Marine Protected Areas in the Irish Sea Equitably Governed and Managed? - Schéré, Constance M.; Schreckenberg, Kate; Dawson, Terence P.; Jones, Nikoleta (Frontiers in Marine Science, 2021)
It is not enough to simply designate a protected area. According to the Convention on Biological Diversity’s Aichi Target 11, these sites should be governed and managed effectively and equitably. Equitable (i.e., fair and inclusive) conservation is vital to ensuring effective protection of natural resources while maintaining human well-being. Yet, equity tends to be overlooked in protected area assessments. Three marine protected areas (MPAs) in Great Britain, Northern Ireland, and the Republic of Ireland were selected to assess equitable governance and management in the Irish Sea. This is one of the first studies to assess equity across multiple stakeholder groups in MPAs. The Site-level Assessment for Governance and Equity (SAGE) toolkit, developed by the International Institute for Environment and Development (IIED) to address the gap in equity assessments, was used to evaluate equitable governance and management in these MPAs. Based on the three dimensions of equity (recognition, distribution, and procedure), SAGE contains Likert-scale questions to assess good governance by evaluating how different stakeholder groups perceive their protected area’s management and how included they feel in decision-making. Quantitative data from SAGE is complemented by qualitative data from semi-structured interviews with stakeholders to understand the impact MPA management has on local communities and MPA users. The results of this study reveal a lack of communication between MPA authorities and local stakeholders. They highlight the need for co-management in the form of inclusive partnerships as an alternative to the current top-down governance approach favoed in the United Kingdom and Ireland.